Increased NFATC4 Correlates With Poor Prognosis of AML Through Recruiting Regulatory T Cells - Zhao, Chong; Yang, Shaoxin; Lu, Wei; Liu, Jiali; Wei, Yanyu; Guo, Hezhou; Zhang, Yanjie; Shi, Jun (Frontiers in Genetics, 2020)
Despite immune responses play important roles in acute myeloid leukemia (AML), immunotherapy is still not widely used in AML due to lack of ideal target. Therefore, we identified key immune genes and cellular components in AML by an integrated bioinformatics analysis, trying to find potential targets for AML. 86 differentially expressed immune genes (DEIGs) were identified from 751 differentially expressed genes (DEGs) between AML patients with fair prognosis and poor prognosis from TCGA database. Among them, nine prognostic immune genes, including NCR2, NPDC1, KIR2DL4, KLC3, TWIST1, SNORD3B-1, NFATC4, XCR1, LEFTY1, were identified by univariate Cox regression analysis. A multivariable prediction model was established based on prognostic immune genes. Kaplan-Meier survival curve analysis indicated that patients in high-risk group had shorter survival rate and higher mortality than in low-risk group (P < 0.001), indicating good effectiveness of the model. Furthermore, Nuclear factors of activated T cells-4 (NFATC4) was recognized as key immune gene identified by co-expression of differentially expressed transcription factors (DETFs) and prognostic immune genes. ATP binding cassette transporters (ABC transporters) was the downstream KEGG pathway of NFATC4, identified by gene set variation analysis (GSVA) and gene set enrichment analysis (GSEA). To explore the immune responses NFATC4 involved, immune gene set of T cell co-stimulation was identified by single cell GSEA (ssGSEA) and Pearson correlation analysis, positively associated with NFATC4 in AML (R = 0.323, P < 0.001, positive). In order to find out the immune cell types affected by NFATC4, the CIBERSORT algorithm and Pearson correlation analysis was applied, and revealed that regulatory T cells (Tregs) has the highest correlation with NFATC4 (R = 0.526, P < 0.001, positive) in AML from 22 subsets of tumor infiltrating immune cells. The results of this study were supported by multi-omics database validation. In all, our study indicated that NFATC4 was key immune gene in AML poor prognosis through recruiting Tregs, suggesting NFATC4 might serve as a new therapy target for AML.